IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY PADA PT. EKADURA SEI MANDINGKABUPATEN ROKAN HULU(Studi Pemberdayaan Ekonomi Masyarakat) - Yosi Witasari; Meyzi Heriyanto (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2022)
Abstract The purpose of this research is to know and analyze the implementation of Corporate Social Responsibility program at PT. Ekadura Sei Manding, Rokan Hulu Regency. This research is qualitative with a descriptive case approach The results showed that there are several indicators that must be considered in the implementation of corporate social responsibility (CSR) program at PT. Ekadura Sei Manding Rokan Hulu Regency is the form and content of policies, organizational capabilities with all its resources and environmental influences. If PT. Ekadura Sei Manding Rokan Hulu Regency cannot meet the 3 (three) indicators, there will be obstacles that can trigger failure in the Implementation of Corporate Social Responsibility program. Therefore, related to the Implementation of Corporate Social Responsibility program at PT. Ekadura Sei Manding Rokan Hulu Regency as a whole has not been running optimally, effectively and efficiently. Factors inhibiting the implementation of corporate social responsibility program. PT. Ekadura Sei Manding includes the improper use of Corporate Social Responsibility (CSR) grants, erratic disbursement of aid funds, the misappropriation of business capital, lack of public awareness in utilizing assistance, lack of knowledge and skills of program implementing employees and weak commitment of company leaders in organizing the implementation of corporate social responsibility programs.